Presidential Debate as a Genre of Strategic Communication - Sheygal, Yelena; lvanova, Julia (Respectus Philologicus, 2004)
The article deals with the phenomenon of strategic communication. The major constituent features of this type of communication are defined: (1) the conflict of the speakers’ goals (the genetic aspect of strategic communication), (2) disclosing a system of influence strategies in discourse (the psycholinguistic aspect) and (3) resolving the conflict of the goals through the culturally determined communicative game form (the cultural aspect). The use of the term "strategic" for this type of communication is argued and justified. The authors provide an example of strategic communication analysis describing the genre of presidential debates according to the above-mentioned aspects, thus suggesting it to be the prototype genre of strategic communication. A multilevel system of influence strategies employed by the candidates for presidency is revealed. It is claimed that the choice of strategies depends on the temporal structure of the dialogue.